ANALISIS REVOLUSI KOMUNIKASI TERKINI DALAM PENERAPAN TEKNOLOGI 5G PADA JARINGAN SELULER BERBASIS GELOMBANG ELEKTROMAGNETIK - Fitriya Ichda Setiawati; Sudarti, Sudarti; Yushardi, Yushardi (Kohesi: Jurnal Sains dan Teknologi, 2023)
The 5G signal technology in electromagnetic pulse networks has triggered a revolution in wireless communication. This wireless technology is more advanced than the previous wireless (1G, 2G, 3G, and 4G). An electromagnetic pulse is a form of electromagnetic radiation made up of both electric fields and magnetic fields moving in unison. 5G operates at a higher frequency than previous cellular technology. The article's main focus is on the link between a 5G signal and an electromagnetic pulse and how the characteristics of the electromagnetic wave affect the performance and range of the signal. Here will be a discussion of 5G operating ata higher frequency range, including millimeters, which provides an extremely high data speed and large capacity. Additionally, it discusses the debate over the health effects of 5G technology and electromagnetic waves, detailed the scientific and global health organization's view of the issue. Research continues to understand and maximize the potential of 5g technologies in coming up with faster and better connections, as well as how we can overcome te's challenges.